PERAN DIGITALISASI AKUNTANSI DALAM EFISIENSI DAN TRANSPARANSI - Nugroho, Mahendra Adhi; Kusumawati, Fadhilah Dian; Buchori, Willa Putri Malinda (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
This research aims to determine the role of accounting digitalization in increasing efficiency and transparency. The research method used is using a qualitative- descriptive approach. The research results show that digitalization of accounting has brought significant changes in increasing efficiency and transparency. Digitalization of accounting emphasizes the automation of routine processes such as recording transactions and preparing financial reports. Automation results in operational efficiency and transparency. In addition, accounting digitization allows access to financial data in real time, supporting efficiency and transparency in organizations. There is no loophole for fraudsters with digitalization because the digitalization process is so fast. Efficiency and transparency will help the accounting profession's duties. This benefit will also strengthen relationships with stakeholders